Association of genetic variations with pharmacokinetics and lipid-lowering response to atorvastatin in healthy Korean subjects - Woo HI; Kim SR; Huh W; Ko JW; Lee SY (Dove Medical Press, 2017)
Hye In Woo,1 Suk Ran Kim,2 Wooseong Huh,3,4 Jae-Wook Ko,4 Soo-Youn Lee4,5 1Department of Laboratory Medicine, Samsung Changwon Hospital, Sungkyunkwan University School of Medicine, Changwon, Korea; 2Clinical Research and Development, Hanmi Pharm. Co., Ltd., Seoul, Korea; 3Department of Medicine, 4Department of Clinical Pharmacology and Therapeutics, 5Department of Laboratory Medicine and Genetics, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul, Korea Background: Statins are effective agents in the primary and secondary prevention of cardiovascular disease, but treatment response to statins varies among individuals. We analyzed multiple genetic polymorphisms and assessed pharmacokinetic and lipid-lowering responses after atorvastatin 80 mg treatment in healthy Korean individuals.Methods: Atorvastatin 80 mg was given to 50 healthy Korean male volunteers. Blood samples were collected to measure plasma atorvastatin and lipid concentrations up to 48 hours after atorvastatin administration. Subjects were genotyped for 1,936 drug metabolism and transporter genetic polymorphisms using the Affymetrix DMET plus array.Results: The pharmacokinetics and lipid-lowering effect of atorvastatin showed remarkable interindividual variation. Three polymorphisms in the SLCO1B1, SLCO1B3, and ABCC2 genes were associated with either the maximum concentration (Cmax) of atorvastatin or changes in total cholesterol or low-density lipoprotein cholesterol (LDL-C). Minor homozygotes (76.5 ng/mL) of SLCO1B1 c.-910G>A showed higher Cmax than heterozygotes (34.0 ng/mL) and major homozygotes (33.5 ng/mL, false discovery rate P=0.040). Cmax and the area under the plasma concentration curve from hour 0 to infinity (AUC∞) were higher in carriers of the SLCO1B1*17 haplotype that included c.-910G>A than in noncarriers (46.1 vs 32.8 ng/mL for Cmax; 221.5 vs 154.2 ng/mL for AUC∞). SLCO1B3 c.334G>T homozygotes (63.0 ng/mL) also showed higher Cmax than heterozygotes (34.7 ng/mL) and major homozygotes (31.4 ng/mL, FDR P=0.037). A nonsynonymous ABCC2 c.1249G>A was associated with small total cholesterol and LDL-C responses (0.23% and -0.70% for G/A vs -11.9% and -17.4% for G/G). The Cmax tended to increase according to the increase in the number of minor allele of SLCO1B1 c.-910G>A and SLCO1B3 c.334G>T.Conclusion: Genetic polymorphisms in transporter genes, including SLCO1B1, SLCO1B3, and ABCC2, may influence the pharmacokinetics and lipid-lowering response to atorvastatin administration. Keywords: atorvastatin, pharmacokinetics, pharmacogenomics, SLCO1B1, SLCO1B3, ABCC2